Malay Medical Tibb Manuscripts from The Perspective of Civilization, Ethics, and Health Rights (Lembaga Contrarius Indonesia, 2026)
This study examines selected Malay Tibb medical manuscripts which namely MSS 813, MSS 845, MSS 1796, MSS 1820, MSS 1875, MSS 1923, MSS 2468(D), and MSS 2483(G), as expressions of a traditional medical knowledge system shaped by Islamic principles and local experience. These manuscripts document herbal formulations, therapeutic practices, and spiritual elements that reflect an integrated understanding of physical and spiritual healing. The study focuses on three analytical dimensions: (i) Malay-Islamic civilizational values embedded in the transmission of medical knowledge, (ii) ethical principles governing medical practice, and (iii) ethical conceptions of health, culture, and spirituality that may be discussed in relation to contemporary human-rights discourse. Employing qualitative textual and thematic analysis, the study examines the selected manuscripts through the analytical framework of maqasid al-shari‘ah, with comparative reference to selected principles of the Universal Declaration of Human Rights (1948). The findings suggest that Malay Tibb manuscripts function not merely as records of traditional medicine but as civilizational texts that integrate medical practice with ethical responsibility, cultural continuity, and spiritual awareness. Rather than projecting modern legal categories onto pre-modern texts, this study demonstrates how the ethical values embedded in these manuscripts resonate with contemporary discussions on access to healthcare, cultural sustainability, and human dignity. The article contributes to manuscript studies, medical humanities, and Islamic ethics by highlighting the relevance of Malay Tibb manuscripts for rethinking holistic and value-based approaches to health in plural and global contexts.